EXCEPTIONS TO LEGALISM BY THE FIGURE OF THE-POLITICAL: A RANCIÃˆRIAN PHILOSOPHICAL EXTRAPOLATION - Muhammad Maulana Hasnan Rasyid (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2022)
This paper analyzes the legal cases, namely Plessy v. Ferguson (1896) and Brown v. Board of Education of Topeka (1954), with the RanciÃ¨rian philosophical approach. Those two cases were chosen because it contains controversial legal facts, namely the issue of racial segregation. The court's decision on Brown v. Board of Education of Topeka (1954) has been an important milestone because it does not follow the precedent in Brady v. Ferguson (1896) that has legitimized racial segregation applied publicly through legal policies. This paper concludes that the subject of the political which carries equality as a axiom of politics can not only emerge from outside the police, it can also emerge from within the mechanism the police itself through the figures of the emancipated judges in the court.